The phenomenon of urban sprawl in modern Poland: Causes, effects and remedies - Karwińska, Anna; Böhm, Aleksander; Kudłacz, Michał (Journal of Public Governance, 2018)
Objectives: The objective of this article is to identify the reasons for the emergence of urban sprawl in Poland, with particular reference to selected medium-sized cities in the Małopolska voivodeship, located at different distances from Kraków. The second objective of this article is to indicate the awareness of the authorities of these cities of the influence of the core city (Kraków) and their efforts to use this phenomenon for their own developmental goals.Research Design & Methods: Documents defining the socio-economic development policies of Limanowa, Niepołomic and Nowy Targ were used for the analysis, as well as selected quantitative data indicating the direction and strength of the urban sprawl. An important element of this article is an indication of the consequences of this phenomenon and remedies for public administration of various levels in Poland. The model of gravitational potential was utilised as the research basis.Contribution / Value Added: As an added value, an attempt should be made to indicate the relation between the values of indicators and the policy of local development (actions of local authorities to eliminate negative effects of the urban sprawl phenomenon).Implications / Recommendations: Although the urban sprawl phenomenon is involuntary (and ubiquitous), it can be controlled, and the lack of actions to control consequences will make them even more acute. Solutions should be systemic in nature and implemented at the level of central administration in Poland, but the attitude of local authorities is also important. In addition, the influence of Kraków on its functional surroundings has a different strength and character. From the point of view of local authorities, it is important to diagnose strength and character (positive or negative) in order to properly choose the direction of the given city’s development policy.